Role of 2nd sphere H-bonding residues in tuning the kinetics of CO2 reduction to CO by iron porphyrin complexes. Issue 18 (4th January 2019) - Sen, Pritha; Mondal, Biswajit; Saha, Dibyajyoti; Rana, Atanu; Dey, Abhishek
Abstract : A series of iron porphyrins that vary only in the distal H-bonding network exhibit turnover frequencies (TOFs) ranging from 1.0 s −1 to 10 3 s −1 . Abstract : Iron porphyrins are potential catalysts for the electrocatalytic and photocatalytic reduction of CO2 . It has been recently established that the reduction of CO2 by an iron porphyrin complex with a hydrogen bonding distal pocket involves at least two intermediates: a Fe(ii )–CO2 2− and a Fe(ii )–COOH species. A distal hydrogen bonding interaction was found to be key in determining the stability of these intermediates and affecting both the selectivity and rate of CO2 reduction. In this report, a series of iron porphyrins that vary only in the distal H-bonding network are further investigated and these exhibit turnover frequencies (TOFs) ranging from 1.0 s −1 to 10 3 s −1 . The experimental TOFs correlate with the H-bonding ability of the distal superstructure of these iron porphyrin complexes and analysis suggests that H-bonding alone can tune the rate of CO2 reduction by as much as 1000 fold. DFT calculations provide a detailed insight into how the, apparently weak, 2 nd sphere interactions lead to efficient CO2 activation for reduction. The ability to tune CO2 reduction rates by changing the H-bonding residue instead of the acid source is a convenient way to tune CO2 reduction electrocatalysis without compromising selectivity by introducing competitive hydrogen evolution reaction or formate generation.